POTENSI PENGEMBANGAN EKOWISATA DI KAWASAN WISATA ALAM BAMBARANO DESA SABANG KECAMATAN DAMPELAS KABUPATEN DONGGALA - Ramadhani, Dafila; Labiro, Elhayat; Mallombasang, Sri Ningsih; Sustri, Sustri (Universitas Tadulako, 2020)
Natural tourism area Bambarano has the object and tourist attraction of nature supported by beautiful natural panorama and the cool air, besides having a tourist attraction, the area has a wealth of flora and fauna as well as the tourism potential that can developed as the beach, estuary or Lake Dampelas, culture, local communities, as well as the beauty of the landscapes. The purpose of this research is to know the potential of the development of Ecotourism In the tourist area of realms of Sabang Village Bambarano Dampelas subdistrict of Donggala. Whereas the usefulness of the research that is expected to give an overview and information to the parties concerned. This research was carried out from December 2018 to 2019 February month In the tourist area of realms of Sabang Village Bambarano Dampelas subdistrict of Donggala. This research uses a two-stage research: qualitative descriptive method using analysis and SWOT analysis. Research results showed the potential for ecotourism in the tourist area of realms of Bambarano village of Dampelas sub-district of Donggala Sabang is the beach, Estuary or Lake Dampelas, Mangrove Forests, the types of Flora and Fauna, while the art and cultures in natural tourism area Bambarano namely Ceremony Adata Sando Ngapang, custom Menembel (Ritual traditionally treatment), Molead/rub the teeth with a stone. Bambarano development strategies In the tourist area of Realms according the SWOT analysis, IE. (1) Develope the potential of the object and tourist attraction such as arts and culture. (2) the development of tourism activities supporting facilities. (3) Hold the improvements and the addition of facilities and infrastructure supporting activities. (4) increase the security around the area by forming the interpreter in order to maintain the security of the vehicle parking visitors who come to the natural attractions are safe.Keywords : Ecotourism, Nature Tourism, SWOT, Natural Tourism Area.